2017
DOI: 10.1002/ejic.201601494
|View full text |Cite
|
Sign up to set email alerts
|

Phase Formation and Solubilities in the Ternary System Ni(OH)2–NiCl2–H2O at 25 and 200 °C

Abstract: The solid/liquid equilibria in the ternary system Ni(OH)2–NiCl2–H2O at temperatures of 25 and 200 °C have been investigated by applying equilibration periods of up to 45 months (3 years and 9 months). The equilibration process was studied by isothermal saturation methods using different solids as starting materials. At 200 °C, Ni2Cl(OH)3 and NiCl(OH) occur as stable phases, whereas a solid solution, NiClx(OH)2–x (ss‐type‐OH), appears as an intermediate phase. At 25 °C, two nickel(II) chloride hydroxide hydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These were carried out at room temperature since lower temperatures usually lead to phases with higher water contents although the formation, transformation and crystallisation of hydroxide salts can take years. 26,27 This procedure led to the successful synthesis of the 2-1-5 phase. The thermal behaviour, as well as the spectral and magnetic properties of this phase, was investigated and the crystal structure was solved from laboratory XRPD data.…”
Section: Introductionmentioning
confidence: 99%
“…These were carried out at room temperature since lower temperatures usually lead to phases with higher water contents although the formation, transformation and crystallisation of hydroxide salts can take years. 26,27 This procedure led to the successful synthesis of the 2-1-5 phase. The thermal behaviour, as well as the spectral and magnetic properties of this phase, was investigated and the crystal structure was solved from laboratory XRPD data.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report (Bette et al, 2015) indicated that four units of crystalline water are removed from NiCl 2 •6H 2 O at ∼80°C. However, it is difficult to remove completely the remaining two units even above 200°C, owing to the formation of a black nickel oxide that is produced via the hydrolysis reaction of NiCl 2 with crystalline water (Liu et al, 2017 (Bette et al, 2015;Bette et al, 2017). Additionally, hydrochloric acid is noted to be present in the gaseous product.…”
Section: Resultsmentioning
confidence: 99%